Mathematical modeling methods in assessing the prospects of export development in the Republic of Tatarstan of the Russian Federation - Yu. A. Shakirova; A. A. Gataullina; N. I. Shamsutdinova (Вестник университета, 2024)
In the conditions of instability of the Russian economy, Russian regions have faced the problem of finding new directions of foreign economic development. Mathematical modeling methods, considering the distance between partner regions and their economies volumes, can be effective tools for solving the problem. The article touches upon the modeling foreign trade relations issues in the Republic of Tatarstan on the gravity models’ basis. The purpose of the study is to identify potential trade partners and assess the prospects for the export relations development in the Republic of Tatarstan. The structure, dynamics, and main directions of exports of the constituent entity have been analyzed. Potential trade partners of the Republic of Tatarstan among the Commonwealth of Independent States countries have been identified using the classical gravity model based on assessing the internal regional product and the distance among the regions. The prospects of foreign trade relations with Belarus and the Republic of Uzbekistan have been assessed. Based on J. Tinbergen’s gravity model models of interaction among the regions have been built and forecast values of export volumes for the short term calculated. It was revealed that the Republic of Azerbaijan can become a potential partner for the Republic of Tatarstan. The analysis of the forecast data on the domestic regional product of the Republic of Tatarstan and the gross domestic product of Azerbaijan in 2023 suggests that the exports volume between these entities is expectedly high.